Baseline Characteristics of Frailty and Disease Stage in Older People Living With CKD - Benignus Logan; Elaine M. Pascoe; Andrea K. Viecelli; David W. Johnson; Tracy Comans; Carmel M. Hawley; Laura E. Hickey; Monika Janda; Allison Jaure; Emarene Kalaw; Charani Kiriwandeniya; Misa Matsuyama; et al. (Kidney International Reports)
Introduction: The GOAL trial, a cluster randomized controlled trial, investigated the effect of comprehensive geriatric assessment (CGA) on frail older people with chronic kidney disease (CKD). This paper describes the following: (i) participant baseline characteristics, and (ii) their relationship with CKD stage and frailty severity. Methods: Sixteen kidney outpatient clinics (clusters) were randomly allocated 1:1 to CGA or usual care. Enrolled frail older people with CKD (Frailty Index [FI] > 0.25; aged ≥65 years or ≥55 if First Nations people) received the intervention allocated to their cluster. CKD was defined as moderate (stages 3 or 4) or severe (stage 5 or 5D), and frailty categorized as moderate (>0.25–<0.36), severe (0.36–<0.45) or very severe (≥0.45). Participant characteristics were analyzed using descriptive statistics. Statistical methods appropriate for type of outcome were used to describe the association of frailty and CKD categories with participant characteristics. Results: Over a 27-month period, 240 people were recruited (55.7% male, 82.9% White/European). Mean age was 76.9 (SD: 6.6) years and median FI was 0.39 (interquartile range [IQR]: 0.32–0.47). The median EQ-5D-5L quality-of-life index score was worse in those with very severe frailty (0.57, IQR: 0.28–0.83) compared to severe frailty (0.85, IQR: 0.67–0.92) and moderate frailty (0.90, IQR: 0.82–0.93) (overall P < 0.001). Median EQ-5D-5L was also worse in those with severe CKD (0.79, IQR: 0.40–0.89), compared to moderate CKD (median 0.87, IQR: 0.73–0.92; P = 0.001). Conclusion: This cohort demonstrated poorer quality-of-life scores in those with more severe frailty and more advanced CKD.